2017
DOI: 10.2174/1573409912666161124144725
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Characterization of a Hypothetical Protein, Rv1288 of Mycobacterium tuberculosis Containing an Esterase Signature and an Uncommon LytE Domain

Abstract: In the present investigation, we bioinformatically confirmed that Rv1288 is most likely a LytE domain containing lipolytic enzyme showing similarity to hormone sensitive lipases/esterases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lyt domain is known to interact with the peptidoglycan moiety of cell wall (Buist et al, 2008). Molecular docking studies also demonstrated that it could bind to the N-acetyl glucosamine moiety of peptidoglycan (Kumar et al, 2017a). The peptidoglycan binding assay suggested that Rv1288 was attached to the cell wall of M.tb by Lyt domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lyt domain is known to interact with the peptidoglycan moiety of cell wall (Buist et al, 2008). Molecular docking studies also demonstrated that it could bind to the N-acetyl glucosamine moiety of peptidoglycan (Kumar et al, 2017a). The peptidoglycan binding assay suggested that Rv1288 was attached to the cell wall of M.tb by Lyt domain.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al, performed the bioinformatics analysis by homology modeling and molecular docking to study the probable role of this protein in M.tb . It was suggested as a probable lipolytic enzyme by in silico experiments (Takayama et al, 2005; Kumar et al, 2017a). The LytE domain was predicted to be responsible for the binding of this protein with mycobacterial cell wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent bioinformatic analysis of the M. tuberculosis genome identified an esterase associated with an N‐terminal domain containing three LysM modules that could help position the enzyme in the cell wall (Kumar, Maan, Singh, & Kaur, 2017), but no experimental data have yet to support this hypothesis. Only two other examples of Corynebacteriales cell wall binding proteins have been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…For the ve in silico tools and servers, ROC analysis revealed a high level of dependability and credibility (Kumar et al, 2017). When two or more tools predicted the same result for HP33, the con dence of prediction was judged high.…”
Section: Evaluation Of Performancementioning
confidence: 98%